2015
DOI: 10.1111/dar.12253
|View full text |Cite
|
Sign up to set email alerts
|

Daily affect variability and context‐specific alcohol consumption

Abstract: Results affirm affect variability as a unique predictor of alcohol consumption, independent of mean affect levels. Yet, it is important to differentiate social context of consumption, as well as type of affect variability, particularly at the between-person level. These distinctions help clarify inconsistencies in the self-medication literature regarding associations between average levels of affect and consumption. Importantly, consistent within-person relationships for both variabilities support arguments th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 23 publications
2
41
1
Order By: Relevance
“…Multilevel models are often complex and analyses on associations between negative affect and drinking are rarely structured in such a way as to test nonlinear associations between negative affect and drinking. It is not uncommon for experience sampling studies to report null, or at least modest associations between negative affect and drinking (Hussong, 2007; Mohr, Arpin, & McCabe, 2015; Swendsen et al, 2000). Although the current study examines changes in negative affect rather than changes in drinking as the outcome, the results suggest that greater attention may need to be given to potential non-linear associations between drinking and NA, with the most robust associations occurring when negative affect is elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Multilevel models are often complex and analyses on associations between negative affect and drinking are rarely structured in such a way as to test nonlinear associations between negative affect and drinking. It is not uncommon for experience sampling studies to report null, or at least modest associations between negative affect and drinking (Hussong, 2007; Mohr, Arpin, & McCabe, 2015; Swendsen et al, 2000). Although the current study examines changes in negative affect rather than changes in drinking as the outcome, the results suggest that greater attention may need to be given to potential non-linear associations between drinking and NA, with the most robust associations occurring when negative affect is elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Although epidemiological studies have highlighted the importance of the relationship within the network between peers at the moment of drug use and on the sharing of injecting equipment (Gyarmathy et al, 2010), drug seeking (Furnari et al, 2015;Linas et al, 2015;Mohr et al, 2015;Shadur, Hussong, & Haroon, 2015) and craving, the human study reported here is the first to explore the nature of the relationship within a dyad of peers, and to correlate it with cocaine consumption. It is also the first to find a direct effect of peer familiarity on drug consumption levels.…”
Section: Influence Of Peer History Of Drug Exposurementioning
confidence: 99%
“…To our knowledge, no study to date has specifically focused on the influence of peer presence, peer characteristics and peer familiarity and their effect on stimulant consumption in humans. The few existing studies in this area only examined the influence of peer presence and close relationships on outcomes such as alcohol use (Mohr, Arpin, & McCabe, 2015) and craving during stressful events (Preston et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dvorak and Simons () enrolled 74 moderate drinkers to respond to fixed and random prompts over a 21‐day assessment period, finding a temporal association between negative mood and alcohol use on drinking days. Mohr and colleagues () enrolled 47 moderate‐to‐heavy drinkers to report affect and alcohol consumption 3 times daily for 30 days, finding that greater negative and positive affect are related to greater daily alcohol consumption.…”
Section: Alcohol‐related Targetsmentioning
confidence: 99%